1988
DOI: 10.1177/002076408803400305
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Relationships of Beliefs About Mental Illness, Psychiatric Diagnoses and Mental Health Care Delivery Among Africans

Abstract: A survey of 50 male and 50 female (N = 100) psychiatric outpatients of Lagos University Teaching Hospital was carried out. DSM III diagnoses of patients was determined from the case notes. Sociodemographic data were also recorded. Findings were analysed for inter-relationships of diagnoses, sociodemographic data and three belief categories (medical, psychosocial and supernatural). The expected predominance of supernatural beliefs was absent; psychosocial responses were greater than the supernatural. There was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 10 publications
0
12
0
1
Order By: Relevance
“…In the few studies involving participants clinically diagnosed with depression, “thinking too much” was frequently used to describe their illness (Abdul Kadir & Bifulco, 2010; Okello et al, 2012; Parker et al, 2001; Patel & Mann, 1997), was named as a primary cause (Ilechukwu, 1988), or was endorsed significantly more by depressed than non-depressed individuals (Rasmussen et al, 2015). Of the studies that named one or more comparative psychiatric diagnoses, approximately one-fifth provided no further explanation or justification for the comparison.…”
Section: Resultsmentioning
confidence: 99%
“…In the few studies involving participants clinically diagnosed with depression, “thinking too much” was frequently used to describe their illness (Abdul Kadir & Bifulco, 2010; Okello et al, 2012; Parker et al, 2001; Patel & Mann, 1997), was named as a primary cause (Ilechukwu, 1988), or was endorsed significantly more by depressed than non-depressed individuals (Rasmussen et al, 2015). Of the studies that named one or more comparative psychiatric diagnoses, approximately one-fifth provided no further explanation or justification for the comparison.…”
Section: Resultsmentioning
confidence: 99%
“…Causal beliefs are usually classified along three dimensions: biological (schizophrenia is a brain disorder due in part to hereditary factors), psychosocial (schizophrenia is caused by external factors such as economic conditions, stressors or level of educational attainment) and magical-religious (schizophrenia originates from supernatural or spiritual forces). In patients with schizophrenia and their caregivers, studies reported a preference for attributing schizophrenia to psychosocial causes in diverse cultures, such as the United Kingdom (Pollock, 1988), Turkey (Karanci, 1995), China (Phillips et al, 2000) Germany (Holzinger et al, 2003) and Nigeria (Ilechukwu, 1988). Supernatural causes were common beliefs in patients with schizophrenia in India (Saravanan et al, 2007; Kate et al, 2012) and Israel (Al-Krenawi, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…[1,5,10-12]]. In a study of Nigerian psychiatric out-patients approximately half of the participants attributed their illness to supernatural causes [10]. All of the 60 patients in Al-Krenawi's study of Bedouin-Arab psychiatric outpatients in Israel attributed their disorder to supernatural causes [1].…”
Section: Introductionmentioning
confidence: 99%
“…In the Nigerian sample referred to above [10] women and the more educated more commonly attributed their illness to psychosocial causes rather than to supernatural causes. However, in Al-Krenawi's study [1] causal beliefs were not related to gender, education, social class or type of illness.…”
Section: Introductionmentioning
confidence: 99%